Learning Lesson Study in Improving Accounting Learning Results - Sihotang, Ijah Mulyani (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to analyze the learning of Accounting with Lesson Study Activities and describe how Accounting learning outcomes by applying Lesson Study-based learning. This research is motivated by the difficulty of students in studying accounting. This is indicated by the low student accounting learning outcomes. The research subjects were 38 students of Accounting Education in Semester II FKIP UMSU. The approach of this research is a descriptive approach, the research procedure is carried out by implementing Lesson Study activities namely Plan, Do and See. The research instrument was in the form of tests and observation sheets. The data analysis technique is descriptive analysis technique. The results showed that accounting learning outcomes were still in the low category with an average score of 70.7, if a range of values was included in the C / B category, while the observations related to students' learning activities fall into the unfavorable category because most students have not maximized in classroom learning activities. If a range of values is entered into the C / B category, while the results of observations related to student learning activities fall into the unfavorable category because most students have not been maximal in classroom learning activities. Individual values indicate better results with a mean count of 80.9